2014
DOI: 10.1111/jpm.12121
|View full text |Cite
|
Sign up to set email alerts
|

The working experiences of novice psychiatric nurses in Taiwanese culture: a phenomenological study

Abstract: Novice psychiatric nurses experience heavy workloads, insufficient training and support in Taiwan. The aim of this study was to understand the working experiences of novice psychiatric nurses during their first year in a clinical setting. A qualitative phenomenological approach, using semi-structured face-to-face interviews was used. Narratives were analyzed using Colaizzi's seven-step method. Data saturation was reached after interviews were conducted with 15 nurses based on the purposive sampling. Four theme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
2
11
0
3
Order By: Relevance
“…These findings may suggest that less experienced nurses more frequently used direct experience as a learning resources to enhance their competence, compared with their experienced counterparts. The findings are consistent with previous studies, which also reported that less experienced professionals learn from practising (Black et al, 2010;Hung et al, 2014;Watling et al, 2012), listening to, observing and rolemodelling others (Hung et al, 2014;Simon and Werner, 1996;Watling et al, 2012). Work experience provides employees with practical, useful, and easily applicable information (Paloniemi, 2006).…”
Section: Discussionsupporting
confidence: 94%
“…These findings may suggest that less experienced nurses more frequently used direct experience as a learning resources to enhance their competence, compared with their experienced counterparts. The findings are consistent with previous studies, which also reported that less experienced professionals learn from practising (Black et al, 2010;Hung et al, 2014;Watling et al, 2012), listening to, observing and rolemodelling others (Hung et al, 2014;Simon and Werner, 1996;Watling et al, 2012). Work experience provides employees with practical, useful, and easily applicable information (Paloniemi, 2006).…”
Section: Discussionsupporting
confidence: 94%
“…A major contributor to these negative feelings was attributed mainly to the perception of the disparity between what is taught in nursing school and what is practiced in reality, or so‐called transition shock. This finding supports prior international studies that highlighted the theory‐practice gap as an important concern among novice nurses . Recent studies also showed that many new nurses suffered transition shock and did not feel prepared for the professional nursing role .…”
Section: Discussionsupporting
confidence: 87%
“…Psychiatric nurses have to work more devoted in line with the needs and expectations of individuals with mental disorders and experience emotional overload. It was stated that exhaustion was more common in psychiatric nurses due to the physical characteristics of the environment, excess number of patients and the propensity for violence of the patients [48]. The emotional exhaustion scores of the mental health workers were found to be high in a different study about the emotional exhaustion in mental health workers [49].…”
Section: Metaphors About Working In the Psychiatry Clinic/ Asaracmentioning
confidence: 99%